(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to clarify the requirements for adopting a competitive strategy (focus strategy, attacka strategy, defense strategy) in real estate bank branches on the Syrian coast. The researcher followed the descriptive approach in her study, and a set of methods, including relying on secondary and primary data, through a questionnaire that was designed by familiarizing the researcher with the published literature, and it was distributed to (144) respondents, from which (141) were retrieved, and (140) questionnaires were suitable for analysis The research community consisted of a cadre of employees in the real estate banking departments on the Syrian coast (branch manager, department heads, divisional heads, and employees), and then the SPSS program was relied upon as a tool for analyzing the available data in order to characterize each of the study axes. The study found that the real estate bank does not focus on excellence in providing a bank- specific banking service to a specific segment of customers, and the real estate bank does not study and analyze the needs and desires of clients. the real estate bank does not implement an integrated marketing strategy that reflects the method and method to achieve marketing goals in the short and long term.